DEFINING WORKPLACE LEARNING - Cacciattolo, Karen (European Scientific Journal, ESJ, 2015)
This paper focuses on the significance of workplace learning. Learning is often defined as the route in which any type of knowledge is attained (Eraut, 2000: 4; Lave & Wenger, 1991: 47). The workplace can be an important place for learning and development, and in which knowledge can be created (Avis, 2010: 171). A discussion of the various types of workplace learning is included in this paper, namely those which fall under the category of formal, informal and unconscious. Research shows that 80% of the learning occurs informally through self-directed learning, networking, coaching and mentoring (Yeo, 2008: 318). However, there may be obstacles that can hinder learning at the place of work. Examples of these obstacles are also tackled in this paper.